Sosialisasi dan Pelatihan Hidroponik Sederhana Untuk Pembelajaran Sains di SMA Negeri 1 Pemali - Palupi, Dora; Susianti, Helda; Siahaan, Limartaida; Dwi Yanti, Yus; Mahmudin; Meliya Ningsih, Riski (Politeknik Negeri Batam, 2025)
Hydroponics is a method of cultivation without soil, but instead utilizes nutrient-rich mineral solutions containing essential elements. This community service activity aims to improve students' skills in creating and maintaining simple hydroponic systems at SMAN 1 Pemali, particularly within the Green Bee extracurricular group. A total of 30 students participated in this activity. The method used in this activity involved socialization and training on simple hydroponics, specifically the wick system. In this activity, in addition to direct practice, students actively engaged in discussions and asked questions, demonstrating their enthusiasm and curiosity about hydroponic plant cultivation. The results of this community service activity include increased knowledge among the students of SMAN 1 Pemali regarding the preparation of hydroponic tools and materials, the preparation of growing media, the planting process of hydroponic pakcoy vegetables, and the monitoring and evaluation of simple hydroponics. The pakcoy plants in the wick system hydroponic produced during practice were distributed to students of SMAN 1 Pemali as a form of appreciation. This activity also raised awareness about the importance of utilizing limited space and recycled materials for plant cultivation through hydroponics. This opportunity has the potential to serve as a foundation for future entrepreneurial ventures.